1999
DOI: 10.1086/314546
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that Members of the Secretory Aspartyl Proteinase Gene Family, in ParticularSAP2,Are Virulence Factors forCandidaVaginitis

Abstract: Virulence of Candida albicans strains with targeted disruption of secretory aspartyl proteinase genes (SAP1 to SAP6) was assessed in an estrogen-dependent rat vaginitis model. Null sap1 to sap3 but not sap4 to sap6 mutants lost most of the virulence of their parental strain SC5314. In particular, the sap2 mutant was almost avirulent in this model. Reinsertion of the SAP2 gene into this latter mutant led to the to recovery of the vaginopathic potential. The vaginal fluids of the animals infected by the wild typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
149
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(158 citation statements)
references
References 40 publications
8
149
1
Order By: Relevance
“…albicans colonizes and infects more host niches in addition to those analyzed in our present study, for example the oral cavity or the vagina. Because the environmental conditions at these sites differ from other locations, C. albicans probably adapts to these niches by the expression of different sets of SAP and other virulence genes (16,30,31), which is supported by the results obtained with specific mutants (32). As a consequence of the differential expression of individual SAP genes at various stages of the infection, one would expect that the individual SAP isoenzymes differ with respect to their biochemical properties, allowing the fungus to use the proteinase that is best adapted to a certain environment and for a specific function.…”
Section: Discussionmentioning
confidence: 69%
“…albicans colonizes and infects more host niches in addition to those analyzed in our present study, for example the oral cavity or the vagina. Because the environmental conditions at these sites differ from other locations, C. albicans probably adapts to these niches by the expression of different sets of SAP and other virulence genes (16,30,31), which is supported by the results obtained with specific mutants (32). As a consequence of the differential expression of individual SAP genes at various stages of the infection, one would expect that the individual SAP isoenzymes differ with respect to their biochemical properties, allowing the fungus to use the proteinase that is best adapted to a certain environment and for a specific function.…”
Section: Discussionmentioning
confidence: 69%
“…The relevance of SAP1±3 for mucosal and cutaneous candidosis has also been illustrated by gene expression studies [6, 9±11] and infection experiments with SAP null mutants [10,11,14,15,21]. The importance of SAP1-3 for infection in vivo is supported by analysis of …”
Section: Discussionmentioning
confidence: 98%
“…Initially it was demonstrated that sap1D, sap2D and sap3D single mutants as well as triple mutants lacking the highly homologous SAP4-SAP6 genes exhibited attenuated virulence after intravenous infection of mice, indicating that all these genes have important roles for the normal progression of a systemic infection Sanglard et al, 1997). Mutants deleted for either SAP1, SAP2 or SAP3 were also found to be less virulent in a rat model of Candida vaginitis, whereas mutants lacking SAP4-SAP6 did not exhibit a detectable virulence defect under these conditions (De Bernardis et al, 1999). Conversely, only the latter mutants showed reduced virulence in a murine model of Candida peritonitis, while deletion of SAP1, SAP2 or SAP3 had no significant effect in this infection model .…”
Section: Introductionmentioning
confidence: 88%